CLINICOMYCOLOGICAL STUDY OF VARIOUS DERMATOPHYTIC INFECTIONS ATTENDING DERMATOLOGY OP IN A TERTIARY CARE HOSPITAL, KANCHIPURAM, - DR.M. ANURADHA; DR.S.THILAK (International Journal of Pharma and Bio Sciences, 2016)
Dermatophytic infections are worldwide in distribution. They often present with superficial skin infections. Severe infections suggest underlying immunodeficiency state of particular clinical case.They are usually caused by anthrapophilic dermatophyte species such as Trichophyton,Microsporum,Epidermophyton. Common age group being 30-40 and males are usually infected. Certain infections are commonly seen in paediatric age group.(T.capitis). The prevalence and distribution of species vary in various geographical areas. Following guidelines for appropriate collection of sample,clinical specimen is collected and 10-20% KOH mount preparation of skin scrapings,hair follicles,nail clippings are examined under microscope for fungal elements,followed by inoculation on to SDA and special dermatophyte media for culture confirmation. Results are interpreted based on colony morphology,microscopic identification of microconidia and macroconidia.The most commonest dermatophyte isolated being T.rubram,T.mentagrophytes followed by T.tonsurans,M.audouinii. Most of the dermatophytic infections are diagnosed and treated depending on clinical manifestations and 10-20% KOH mount.Dermatophytic infections that need prolonged antifungal therapy and those with atypical clinical presentation need confirmation by culture as it takes long time for their isolation Proper identification needs appropriate sample collection Among superficial skin infections dermatophytic infections are the most common.As their infection results in disfigurement and discomfort and significant morbidity ,avoiding contact with infected animals and persons as well as maintaining good environmental , personel hygiene can decrease dermatophytic infections.